Konsep Pendidikan Islam dalam Surah Al-Mujadalah - Achyar Zein; Syamsu Nahar; Muchlis Muchlis (Nazhruna: Jurnal Pendidikan Islam, 2019)
This study aims to analyze: 1) What is the concept of Islamic education according to experts of eduction, and 2) How is the concept of Islamic education contained in surah al-Mujadalah. This study uses qualitative methods, using a library research approach (library research). Primary data sources in this study are Tafsir al-Misbah by M. Quraish Shihab and Tafsir al-Wasith by Wahbah Zuhaili. Research results show that: 1) The concept of Islamic education according to Ibn Khaldun, Ibn Sina, and Al-Ghazali is not the same. In the curriculum, the three experts have different classifications in the translation of knowledge. The classification of knowledge from Al-Ghazali's thought is very detailed, in addition he also added five aspects of education related to science. 2) The concept of Islamic education in Al-Mujadalah letter consists of: educational objectives, educational material, and educational methods. The purpose of Islamic education contained in surah al-Mujadalah is that humans should be obedient to Allah. Educational material consists of: Secret Adab talks, Courtesy (Attending the Assembly of the Prophet), and Prohibition of Making Friends with People Who Are Hostile to Islam, while the Educational method consists of: Story Method, Targhib and Tarhib Method, Advice Method, and Writing Method.